Hubungan Antara Body Image Dengan Pola Makan Dan Status Gizi Remaja Putri Di SMP Al Islam 1 Surakarta - Verawati, Ratna, Ir. Listyani Hidayati, M.Kes, Pramudya Kurnia, STP, M.Agr (2014)
Introduction: Perception of teenagers towards body image can determine the diet and nutritional status. There is a significant positive relation between the perception of body image and the frequency of eating. Purpose: This study aimed to determine the relation between body image and eating patterns with nutritional status of adolescent girls in junior high school Al Islam 1 Surakarta. Method: This was an observational study with cross sectional approach. The number of respondents were 60 girls in junior high school Al Islam 1 Surakarta obtained with simple random sampling method. The body image and eating habits were collected through questionnaires, while the nutritional status data obtained by weighing and height measurement. Data were analyzed using Chisquare. Results: The results of univariate analysis showed that children with positive body image group had usual eating patterns 62,8% but only 25,7% have normal bodyweight, and 60% underweight nutritional status, negative body image group having an unusual eating patterns 72% and 44% overweight nutritional status . There is a relation body image and eating patterns (p = 0.008) as well as nutritional status (p = 0.010) Conclusion: There is a relation body image of adolescent girls in junior high school Al Islam 1 Surakarta and eating patterns and nutritional status